OPTIMALISASI STRATEGI SEKOLAH UNTUK PENINGKATAN KUALITAS PENDIDIKAN DIGITAL ABAD Ke-21 - Ade Tutty Rossa; Hera Asriana; Didah Nuraidah; Elis Sukmawati; Rani Melina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology in the 21st century requires educational units to optimize school strategies in creating adaptive, innovative and relevant learning. This research aims to analyze the optimization of school strategies through technology integration, increasing educator competence, and the use of the PDCA (Plan–Do–Check–Act) sustainable management model. Using a qualitative approach to case studies located at SDN Ciranjang Girang 2 and SDN Pangestu, data collection was carried out through in-depth interviews, observation and documentation studies. The research results show that both schools have made significant efforts in the aspects of digital planning, implementing blended learning, strengthening TPACK-based teacher competencies, and utilizing analytical learning in the evaluation process. However, challenges related to infrastructure, teacher resistance, and limited digital devices are still the main obstacles. This research concludes that optimizing school strategies must be carried out in an integrated manner through increasing human resource capacity, updating school policies, and external environmental support. The research results provide a model of recommended strategies that elementary schools can use in implementing sustainable digital education.